Association between frailty and vitamin B12 in the older Korean population. Issue 43 (23rd October 2020) - Soh, Yunsoo; Won, Chang Won
Abstract : Abstract: Frailty is a common geriatric condition due to aging and defined as a decline in strength and a decrease in the physiologic ability to maintain the homeostasis. Vitamin B12 (B12), water-soluble vitamins, are a cofactor in DNA synthesis and involved in the metabolism of every cell in the human body, including the central nervous system. Demyelination neuromuscular symptoms observed in the peripheral nervous system, along with signs of significant damage to nerve fibers, often cause weakness, numbness in distal limbs, impaired balance, gait ataxia, and even physical frailty. In this cross-sectional study, we aimed to investigate the relationship between frailty and B12 level in community-dwelling Korean older adults. Using the data from the Korean Frailty and Aging Cohort Study, 2938 participants (1400 men and 1538 women) were recruited in this study. To evaluate frailty, we compared the frail group and not-frail group based on the modified Korean version of the cardiovascular health study frailty index developed by Fried. SARC-F is used to screen for sarcopenia. The short physical performance battery (SPPB) timed up and go (TUG) test and activities-specific balance confidence scale used to evaluate the physical function and fall risk of participants. B12 concentrations were classified into clinically relevant categories: insufficient (<350 pg/mL) and sufficient (≥350 pg/mL). Linear and logistic regression analyses were used to evaluate the relationship between frailty and B12 levels. The mean age of the frail group was 77.8 (standard deviation = 3.7) years, while that of the not-frail group was 76.7 (SD = 4.0); of which the frail group's mean age was significantly high. In the unadjusted model, frailty was highly prevalent in the B12 insufficient group (odds ratio = 1.298). In the model fully adjusted for demographic data and comorbidities, these associations were attenuated. The B12 sufficiency group showed better total SPPB and TUG test scores. However, they were not statistically significant in the fully adjusted model. In this cross-sectional study, low B12 increased the incidence of frailty and affected physical performance, but it does not increase the incidence of frailty when considering the confounding factors. Frailty is caused by several factors rather than 1 factor, and B12 is one of these factors.